A formação continuada na perspectiva da coordenação pedagógica de docentes dos anos iniciais do Ensino Fundamental - Bellintani, Irinilza Odonor Gianesi (2019)
The complexity of contemporary society, with scientific advances, new forms of communication, economic crises, conflicts, movements for equity of rights and improvement of the quality of life, presents many uncertainties with consequences in education, since it constitutes the process that humanizes people to build and ensure the maintenance of a more fair society. School education, influenced by the conjunctural conditions of society, is called to respond to the challenges that are presented. In the last three decades, we have seen a growing literature and research on the role of the pedagogical coordinator as an articulator of the school work and, above all, as a teacher trainer in times of intense transformations that highlight the importance of critical thinking, autonomy, responsibility, coherent, intentional action and committed to quality education. Based on theoretical references that discuss the performance of pedagogical coordinator and the continued formation in the context of work as: Alarcão (2003), Almeida (2001, 2011, 2012, 2013, 2015, 2016) Bruno & Cristov (2015, 2016), Canário (1998, 2012), Cristov, Ronca & Terzi (2012) Fujikawa (2006, 2015), Fullan & Hargraves, (2000), Imbernóm (2009, 2011), Nóvoa (2007), Placco (2004), Placco & Souza (2006, 2016, 2017) the present work aims to "analyze experiences of continuing education in private schools, with teachers from the initial years of Elementary Education, from the perspective of the pedagogical coordinator". Through semi-structured interviews with four coordinators of private schools in the city of São Paulo, we investigated the coordinator's role in the continuing education of educators. The information collected in the interviews was treated based on the Content Analysis, which is the theoretical methodological reference. Four categories were defined to analysis and discussion of the results. It is important to emphasize the relevance of institutional culture in favor of collective work, the complexity of pedagogical coordination, suggesting the effective action legitimized by the coordinator's professional competence, the diversity of themes and forms of groupings for training, with emphasis on study and definition of what and how to teach, the importance of listening, situational analysis and the consideration of everyday facts in order to inspire potent interventions. The PC's awareness of their interference with actions in the identy constitution of educators and sensitivity and attention to the evidences expressed by the various actors of the process on the effectiveness of its formative action are also highlighted. It is recommended to use effective data to analyze results of the training processes at school